Exploring the perceptions of people with dementia about the social robot PARO in a hospital setting. (February 2021) - Hung, Lillian; Gregorio, Mario; Mann, Jim; Wallsworth, Christine; Horne, Neil; Berndt, Annette; Liu, Cindy; Woldum, Evan; Au-Yeung, Andy; Chaudhury, Habib
New technology, such as social robots, opens up new opportunities in hospital settings. PARO, a robotic pet seal, was designed to provide emotional and social support for older people with dementia. We applied video-ethnographic methods, including conversational interviews and observations with video recording among 10 patient participants while they were using the robot. We also conducted semi-structured individual interviews and focus groups with nursing staff to gain contextual information. Patient and family partners were actively involved in the study as co-researchers. This study reports our findings on the perceptions of 10 patients with dementia about their experiences with PARO in a hospital setting. Thematic analysis yielded three substantive themes: (a) 'it's like a buddy' – the robot helps people with dementia uphold a sense of self in the world, (b) 'it's a conversation piece' – the baby seal facilitates social connection and (c) 'it makes me happy' – PARO transforms and humanizes the clinical setting. Our findings help provide a better understanding of the perspectives of patients with dementia on the use of social robots.